Giant Heart of Classical Infantile-Onset Pompe Disease With Mirror Image Dextrocardia. (September 2015) - Tripathi, Sushil P.; Phadke, Milind S.; Kerkar, Prafulla G.
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.